Assessing the Validity and Effectiveness of Student Worksheets and Creativity Tests in Enhancing the Creativity of Open University Students - Dwikoranto, Dwikoranto; Surasmi, Wuwuh Asrining; Suparti, Suparti; Setiani, Rahyu (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
This research aims to create valid and effective Student Activity Sheets (SAS) and Scientific Creativity Tests (SCT) in order to enhance the creativity of open university students. The validity of SAS and SCT is determined by achieving a minimum score of 2.50 in both content validity and construct validity categories. Similarly, their effectiveness is measured by: (1) observing a statistically significant increase in students' scientific creativity at a 5% significance level; and (2) achieving a minimum average n-gain in the medium category. This research follows an Educational Design Research approach and utilizes a pre-experimental design with a one-group pre-test and post-test design. The research subjects consist of undergraduate students at Open University Surabaya during the 2023/2024 academic year. The data collection instruments used in this research include: (1) a Validity Assessment Sheet for SAS and SCT; and (2) the SCT test. The research data, which includes pre-test and post-test scores, are collected after conducting prerequisite tests such as normality and homogeneity tests. These scores are then analyzed using a paired t-test to identify any differences in students' scientific creativity between the pre-test and post-test stages. The average level of improvement in scores is calculated using the normalized gain (N-gain) method. The research data, in the form of scores obtained from the assessments of the validity of learning tools by three Learning Experts, are analyzed using the average method to determine validity, as well as by using Cronbach's alpha (Î±) to assess reliability. The same analysis is conducted for the Research Instrument scores. The research findings demonstrate that both SAS and SCT tools are valid and effective in enhancing student creativity.